PENERAPAN MODEL ARIMA DALAM MEMPREDIKSI HARGA EMAS - Lolyta Damora Simbolon (MES: Journal of Mathematics Education and Science, 2022)
Gold is one of the investment commodities that has been in great demand by the public for a long time because, in addition to bringing profits, gold investment is also considered safe. To get the best profit from the gold investment, forecasting and planning can be done to predict the gold price. In this research, the best forecasting model will be determined in the price of 1 gram gold bullion produced by PT. Aneka Tambang (ANTAM) using the ARIMA method to predict gold prices in 2022. From the results of the discussion, the appropriate model to predict gold prices is ARIMA(4,2.0). ARIMA value(4,2,0) with error value at MAD= 6220.55, MAPE= 0.6624, MSE=47274070.87, RMSE=6875.61